RELASI HUKUM, MORAL DAN HAK KEKAYAAN INTELEKTUAL (ANALISIS KONTROVERSI HUKUM DAN MORAL REKAYASA GENETIKA MAKHLUK HIDUP DI INDONESIA) - Muhammad Syaifudin; Sri Handayani (Jurnal Dinamika Hukum, 2014)
The development of genetic engineering is remarkably developed. Even it has been able to duplicate animals, and potentially to do so in human being by using  cloning technology which provokes controversy in terms of legal and moral matters. In regard to this, it is important to conduct a legal research based on hermeneutic paradigm, by employing interdisciplinary approach. Then, the research materials consist of law materials and social facts. The results of this research are: the first, the genetic engineering contains legal and moral controversies in Indonesia because of its negative impacts; the second, the genetic engineering has a philosophical, juridical and dogmatic basis of law to be acknowledged and protected by law of intellectual property rights; and the third, reformulation of legal arrangement on genetic engineering in Indonesia has to reinforce the philosophical basis, refer to the juridical consideration as well as sociological view. Key words:  controversy, legal, moral, genetic engineering, human being and intellectual property rights.